Navigating Breast Cancer Screening in Rural Missouri: From Patient Navigation to Social Navigation. Issue 2 (17th February 2022) - Hunleth, Jean; Steinmetz, Emily
ABSTRACT: The National Cancer Institute recently identified rural cancer disparities as a priority issue, dedicating resources to rural cancer prevention, presenting opportunities and also risks. We bring an anthropological concept, social navigation, to bear on a popular public health intervention, patient navigation, increasingly proposed as an "evidence-based" approach to reducing health disparities. Our study of mammography in the Missouri Bootheel demonstrates how such interventions elide the shifting terrain and slow violence of rural health care where people must improvise care through trying out or sticking with providers, negotiating self-advocacy and deference, or changing screening timelines amidst structural constraints and rural stereotypes.